Partnerships for Entrepreneurial Success: A Validation Study of the School-Family-Community Partnership Scale in Vocational Education - Timan, Agus; Maisyaroh, Maisyaroh; Benty, Djum Djum Noor; Adha, Maulana Amirul; Valdez, Anabelie Villa; Lesmana, Indra (International Review of Management and Marketing, 2025)
This study intends to validate the School-Family-Community Partnership (SFCP) Scale in advancing entrepreneurial paths among Indonesian vocational graduates. The SFCP model emphasizes the collaborative efforts of schools, families, and communities in fostering entrepreneurship among students. Given the unique socio-cultural context of Indonesia, this research addresses the need for a validated scale to measure the effectiveness of these partnerships in vocational education settings. 360 students from Indonesian vocational high schools participated in this study. Three main dimensions— Educational Support (ES), Family Support (FS), and Community Support (CS)—were found by means of exploratory factor analysis (EFA) and confirmatory factor analysis (CFA). The findings indicate that these dimensions significantly contribute to students’ entrepreneurial aspirations, with Educational Support emerging as the most influential factor. The scale exhibited strong reliability and validity, establishing it as a reliable instrument for future research in entrepreneurship education. Emphasizing the need of combining educational, familial, and community assistance in developing entrepreneurial careers among vocational students, this study offers important insights for teachers, policymakers, and community leaders.